(untitled) (Global Journal of Science Frontier Research, 2014)
The Isomorphic Shell Model is applied to the first three neutron shells in searching for possible stability there It has been found that the even neutron nuclei 4 n -16 n show possible stability, some of which exhibit stable excited states as well.